The Influence of Peer Environment on Student Learning Outcomes at the High School Level - Achmad Irsyadul’ Ibad; Didit Darmawan (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2026)
Peers as social elements have an important role in shaping the learning achievement of high school students. Adolescents in general interact intensely with their peers which can influence their attitudes, motivation to learn, and daily activities. Therefore, this study examines the impact of peer environment on the learning outcomes of high school students. Using qualitative methods with literature studies. Data was obtained through literature searches from scientific books, national and international journals, as well as relevant previous research related to peer interaction and learning processes. The analysis was carried out in a descriptive-qualitative manner through identification, grouping, and interpretation of findings from the literature. The findings of the analysis indicate that the peer environment has a positive and significant impact on the learning achievement of high school students. If the interaction is positive, then the motivation to learn increases, students become more active in the classroom, and learning habits become better. However, if the social environment is negative, interest in learning decreases and academic achievement also decreases. Schools should create a conducive social environment through collaborative learning, academic group activities, and strengthening a positive learning culture. Thus, if managed properly, the learning outcomes of high school students can be optimized optimally and sustainably.